Content Marketing, Influencer Marketing, dan Ulasan Online Mendorong Minat Beli Skincare - Danar Adi Wijanarko; Arina Mana Sikana; Rindy Pramitha Sari; Krisnawati Krisnawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the impact of content marketing, influencer marketing, and online customer reviews on the purchasing interest in Skintific products on TikTok among Generation Z students of the Bachelor of Management program at Universitas Semarang. Primary data was collected through a Google Form questionnaire distributed to Generation Z students using purposive sampling technique, based on the criteria of Generation Z age, active TikTok users, and familiarity with Skintific products. A quantitative approach was applied using multiple linear regression analysis after validity, reliability, normality, multicollinearity, and heteroscedasticity tests met the requirements. The results show that content marketing, influencer marketing, and online customer reviews individually have a significant positive effect on purchasing interest in Skintific products. Simultaneously, these three variables significantly influence purchasing interest, with a strong contribution. These findings imply that an integrated digital marketing strategy involving content marketing, influencer marketing, and online customer reviews is effective in increasing purchasing interest among Generation Z students on TikTok. This provides valuable insights for companies in designing more effective digital marketing campaigns to attract young consumers through social media platforms.